Uncomfortable Television - Hargraves, Hunter, 1983- (Book collections on Project MUSE., 2023)
"Uncomfortable Television examines the affects of late capitalism through its most dominant media form, television. Hunter Hargraves examines postmillennial American television and charts the reorganization of its affective structures and the aesthetic, formal, industrial, technological, and generic shifts behind these changes. At its core, Uncomfortable Television makes a historical claim: that American television in the early-21st Century produces a pleasurable discomfort within its spectators that bears witness to the sedimentation of neoliberal culture. In marrying changes in TV form, genre, technology, and criticism to key affects of discomfort, television helped its audiences embrace discomfort within the rhythms and social structures of late capitalism. Turning discomfort into pleasure thus became an instrumental strategy of the media industries to mold the viewing public into one concerned with individual freedom and economic flexibility. Turning to a wide variety of popular and critically acclaimed television texts that epitomize the changes to postmillennial American television, Uncomfortable Television reads these texts as key constellations in a national structure of feeling defined in terms of rerouting discomfort into pleasure."--